FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PEMILIHAN METODE AKUNTANSI PERSEDIAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Ulfi Hidayah, 14.05.52.0274; Susilowati, Yeye (Students' Journal of Economic and Management, 2019)
This study aims to analyze the factors that influence the selection of inventory accounting methods in manufacturing companies listed on the Stock Exchange in 2014-2017. The independent variables used in this study are company size, inventory variability, inventory intensity, variability in cost of goods sold, financial leverage, and liquidity. While the dependent variable used in this study is the inventory accounting method in accordance with PSAK No. 14 (2018), namely the FIFO inventory method and the average. The population used in this study is a manufacturing company listed on the Indonesia Stock Exchange in 2014-2017. The method of sampling in this study was purposive sampling method with a total sample of 280 companies. The analytical tool used is logistic regression analysis using the IBM SPSS version 21 program. The results showed that the variability of cost of goods sold and liquidity had a significant influence on the selection of inventory accounting methods. While company size, inventory variability, inventory intensity, and financial leverage do not significantly influence the selection of inventory accounting methods.